Power system scheduling in presence of renewable energy and energy storage - Pazheri, Faisal Rahiman (2015)
Power system scheduling problems like unit commitment and power dispatch methods have a vital role in the operation of electric power industry. Nowadays, global electricity consumption is growing rapidly while the supply of fossil fuels is dwindling and the concern about global warming is increasing. Therefore, power utilities are being forced to use hybrid power systems that consist of both conventional and renewable generation units. Optimum scheduling of such hybrid systems with Energy Storage Facilities (ESF) can ensure a consistent level of renewable power penetration throughout the operation periods, and thus, an economic, clean and energy efficient power generation can be achieved. Modelling of power system scheduling for hybrid power systems with ESF, optimization of such system’s scheduling and applications of scheduling under different scenarios are the main scopes of this thesis. The importance and applicability of this research are analyzed and illustrated by MATLAB simulations with the aid of suitable algorithms using the data of several hybrid test systems. It is shown that the proposed scheduling models led to effective utilization of the available resources resulting in significant savings in operation cost and reduction in pollutants emissions, etc. The proposed power dispatches on a hybrid system using IEEE-30 test bus data shows that more than 30% of fuel costs, pollutants emissions and transmission losses can be reduced with 30% renewable penetration. Moreover, more than 10% saving in fossil fuel utilization and above 50% pollutants emissions can be achieved if the proposed approach is applied to energy efficient power generation method with 15% of renewable penetration. This research will help the power utilities to use available energy resources effectively and encourage them to increase the utilization of green energy.